Body composition analysis of athletes from the elite of Brazilian soccer players - Gerosa-Neto, José [UNESP]; Rossi, Fabrício Eduardo [UNESP]; Silva, Camila Buonani [UNESP]; Campos, Eduardo Zapaterra [UNESP]; Fernandes, Rômulo Araujo [UNESP]; Freitas Júnior, Ismael Forte [UNESP] (Desafio Singular, Lda, 2014)
This study analyzed the body composition and bone mineral density of elite Brazilian soccer players and compared its differences according to the player position. Eighty-two soccer players competing at Brazilian first division were split according to their field positions: Goalkeepers (GK, n= 10), Back-fielders (BF, n= 10), Lateral-midfielders (LM, n= 15), Central-midfielders (CM, n= 25), Forwards (FW, n= 22), and a Control Group (CG, n= 72) of university students. To estimate fat free mass (FFM), fat mass (FM), percentage of body fat (%FM), fat free mass of legs (FFM-Legs) and bone min-eral density (BMD), a DEXA was selected. The positions LM (10.5 ± 5.2), CM (9.7 ± 4.0) and FW (9.9 ± 4.4) had lower values of FM and %FM than the GK (17.3 ± 6.0) and the control group (15.0 ± 5.3). Compared to the other positions, FFM was higher in the GK (68.2 ± 10.9) and BF (64.6 ± 6.8) (p< 0.05). All the soccer players were different from the CG (p< 0.05). Soccer players have an FFM, FFM-Legs and BMD significantly higher and FM and %FM lower than the control group.
Keywords: Athletes; Bone density; DXA; Muscle mass